The Tort of Medical Errors: A Change in Perspective - Oracion, Stephanie Anne V. (Diliman, Quezon City, Philippines: University of the Philippines College of Law)
The tort system has been used to determine negligence in medical malpractice cases. When a plaintiff is able to prove his claim through a preponderance of evidence, and a finding of fault is made, the tortfeasor is made liable and adjudged to pay damages, and sometimes results in the revocation of the license of the physician. Because of advances in medicine and the complex issues involved in both knowledge and practice, it may be proper to explore other means of dealing with professional error. There are some factors outside of human error which commonly considered that may influence the actions of physicians and, in turn, may affect outcomes, whether good or adverse. Injury is not always a result of fault or negligence but it may arise because of a series of events that converge to an adverse outcome. Alternative avenues for dispute resolution may better address these issues in order to come up with uniform standards for compensation, and the achievement of the goal towards prevention of injury in the future.
Keywords: Medical personnel - Malpractice